Pengaruh struktur modal dan profitabilitas terhadap nilai perusahaan studi kasus pada perusahaan sub sektor transportasi yang tercatat di bursa efek indonesia periode 2014-2018 - Tarmedi, Eded; Reghinasalwa Putri, Tissa (Journal of Business Management Education (JBME), 2020)
The purpose of this research is to determine the influence of capital Srtuktur and profitability on the company's value. The research method used in this study is a verivikative dexective method. Data used by secondary data is a data type that is obtained indirectly from the first source (the company) in the form of the company's financial statements for five years (2014-2018). Sampling techniques based on purposive sampling obtained as many as 30 companies. Analysis of the data used verivikative descriptive analysis. After the decryptive data is obtained then a statistical test. The results showed that the capital structure measured using the DEBT to Equity Ratio (DER) indicator and the profitability measured using the Return On Equity indicator have an influence on the company's value measured using the Price to Book Value indicator in the transportation sub-sector company. Where the capital structure has no effect and is not significant to the company's value while profitability affects the value of the company.